ナンキョク タイキ チュウ ノ サブミクロン エーロゾル ノ リュウケイ ブンプ ニ ツイテ - 伊藤, 朋之; イトウ, トモユキ; Ito, Tomoyuki (1982)
P(論文) 1978年8月から12月まで約5カ月間, 南極昭和基地において, エーロゾルの粒径分布の観測を行った。拡散管とポラックカウンターからなる自動測定器および, 光散乱型粒子計数器を用いて, 半径2×10^<-7>～10^<-4>cmの粒径範囲の1時間毎の粒径分布を測定した。12月の月平均粒径分布(dn/d log r)は, 半径5×10^<-7>cmと4×10^<-6>cmに峯を持つ二峯分布であった。この分布から算定すると, 空気1(cm)^3中に含まれる粒子の総個数は450個でそのうち100個は10^<-6>cm以下の半径で, 残りの大部分は10^<-6>～10^<-5>cmの半径であった。粒子の表面積の総量は1×10^<-8>(cm)^2,総体積は1×10^<-13>(cm)^3であった。このような二峯分布は, 多少の違いはあるが, どの月にも一般的に現れた。月による違いは, 半径4×10^<-6>cm近くの峯において顕著にみられ, 峯の高さは8月から12月に向かって高くなった。半径5×10^<-7>cm近くの峯はほぼ一定であった。観測された粒径分布が定常的に存在するためには, 少なくとも10^<-4>(cm)^<-3> s^<-1>程度の発生率で新粒子が連続して発生している必要がある。今回の結果から, 清浄な南極大気中で光化学的に作られる蒸気物質(おそらくH_2SO_4)の無核凝結や有核凝結が, 南極サブミクロンエーロゾルの起源として重要であることが推論できる。さらに研究を進めるためには, SO_2およびその先駆的な気体の濃度や, SO_2からH_2SO_4への変換率などの, 南極における実測が望まれる。 Size distributions of submicron aerosols at Syowa Station (69°00'S, 39°35'E), Antarctica were measured for about 5 months from August to December in 1978. An optical particle counter and an automatic size spectrometer which consists of diffusion pipes and Pollak counters were used. The size distributions over the radius range between 2×10^<-7>cm and 1×10^<-4>cm were determined hourly during the period except when the air was contaminated by local sources. The size distribution averaged for December has a bimodal structure with modal radii at 5×10^<-7>cm and 4×10^<-6>cm. The number of aerosol particles contained in 1(cm)^3 air was 450 including 100 particles whose radii were smaller than 10^<-6>cm. The total surface area of the particles was 1×10^<-8>(cm)^2,and the total volume 1×10^<-13>(cm)^3. Similar bimodal distributions were commonly found in each month. The spectral density of size distribution around the largest modal radii increased from August to December, whereas that around the smallest modal radii did not show any detectable change during the period. In order to explain the observed size distribution is required a continuous production of new particles at an average ...